Intermolecular and surface forces - Israelachvili, Jacob N. (Burlington, MA : Academic Press, 2011)
This reference describes the role of various intermolecular and interparticle forces in determining the properties of simple systems such as gases, liquids and solids, with a special focus on more complex colloidal, polymeric and biological systems. The book provides a thorough foundation in theories and concepts of intermolecular forces, allowing researchers and students to recognize which forces are important in any particular system, as well as how to control these forces. This third edition is expanded into three sections and contains five new chapters over the previous edition. starts from the basics and builds up to more complex systems covers all aspects of intermolecular and interparticle forces both at the fundamental and applied levels multidisciplinary approach: bringing together and unifying phenomena from different fields This new edition has an expanded Part III and new chapters on non-equilibrium (dynamic) interactions, and tribology (friction forces)
Part I: 1. Historical Perspective -- Part II: 10. Unifying Concepts in Intermolecular and Interparticle Forces -- Part III: 19. Thermodynamic Principles of Self-Assembly.
Includes bibliographical references and index.
Keywords: Intermolecular forces; Surface chemistry